A spatial analysis of health status in Britain, 1991–2011. (January 2019) - Dearden, Emily K.; Lloyd, Christopher D.; Catney, Gemma
Abstract: Using Census-derived data for consistent spatial units, this paper explores how the population of Britain in 1991, 2001 and 2011 was spatially structured by self-reported health including exploring the trajectories of change. This paper uses consistent small area units to examine the changing spatial structure of census-derived Limiting, Long-Term Illness (LLTI) in Britain over the twenty year period and utilises the 2011 Office for National Statistics Output Area Classification (OAC) as a geodemographic indicator. The results allow the geography of change to be captured, highlighting how health is inextricably linked to geography, demonstrating quantitatively a complex, yet distinctive, spatial organisation of health inequalities within Britain. Overall decreasing unevenness values, coupled with increased positive spatial association suggests that neighbouring areas have become more similar over time – the distinction between areas characterised by poor health or by good health is decreasing. Highlights: Health inequalities are distinctively spatially organised within Britain. Britain is now more visibly divided by its geography of long-term illness. Distinct spatial concentrations of good and poor health correspond with area type.